Pengaruh Sikap Budaya Kerja Dan Motivasi Kerja Terhadap Kompetensi Guru Di Sekolah Thama Vitya Mulniti Yala Selatan Thailand - Syuhadah Che Wae; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract A school is an educational organization that aims to frame the school's mission, manage teaching and learning, and train teachers as well as students to achieve the same goals. Nowadays, many schools identify the problem of "Human" because it plays a significant role in the organization. With policies that focus on human resources, the executives who are responsible for certain jobs and the recruitment system for human resource development will be determined. The purpose of this research is to describe the Attitude, Work Culture and Motivation, to know and analyze the effects of Attitude, Work Culture and Motivation, to know and analyze the effects attitude on teacher competence, To know and analyze the effects of work culture on teacher competence, to know and analyze the effects of motivation on teacher competence. Research shows that Attitudes, Work Culture and Motivation experiences are simultaneously positive and significant to the teacher competence variables, Attitude has aIpositiveIandIsignificant impact on teacher competence, WorkIculture hasIa positiveIand significant impact on teacher competence, Motivation hadIa positiveIandIsignificantIimpact on preparedness to enter the work world.Keyword: Attitudes, Work Culture, Motivation, Teacher Competence.